The impact of high-intensity resistance training on intraocular pressure and ocular hemodynamics: A literature review - Piórkowska, Iga; Piotrowski, Karol; Jerczak, Małgorzata; Pluszyński, Tomasz; Padula, Natalia; Polewka, Mikołaj; Polańska, Aleksandra; Paczosa, Kacper; Przybył, Filip (Quality in Sport, 2026)
Background. Intraocular pressure (IOP) is influenced by physiological stressors, including resistance exercise (RE). While physical activity is generally protective, high-intensity strength training may induce significant acute IOP spikes, posing a risk for individuals with or at risk of glaucoma. Aim. This systematic review evaluated the acute effects of RE on IOP in healthy adults and identified physiological and methodological factors influencing these fluctuations. Material and methods. A systematic review was conducted using PubMed, Web of Science, and Scopus. Selection criteria included quantifiable exercise intensity (e.g., % 1RM) and standardized IOP protocols. Data analyzed the influence of the Valsalva maneuver (VM), muscle mass, and measurement timing (intra- vs. post-exercise). Results. RE-induced IOP changes are intensity-dependent; loads exceeding 80% 1RM cause spikes up to 200% (exceeding 40 mmHg) when measured during effort. A methodological discrepancy was identified: intra-repetition measurements reported hypertensive peaks, whereas post-exercise assessments showed rapid stabilization or hypotension. The VM was a dominant factor magnifying IOP elevations due to impaired venous drainage. Conversely, Blood Flow Restriction (BFR) training appears to be a safer alternative, eliciting hypertrophy at lower intensities with minimal impact on ocular hemodynamics. Conclusions. Acute RE induces a biphasic IOP response: an extreme, transient increase during exertion followed by rapid stabilization. Traditional post-exercise measurements significantly underestimate the mechanical stress on the optic nerve. High-intensity lifts with the VM should be approached with caution in clinical populations. Future longitudinal research is required to determine the cumulative effects of repeated acute IOP spikes on optic nerve integrity.